Framework for Operational Resilience in Engineering and System Test (FOREST) Part II: Case Study – Responding to "Security as a Functional Requirement". Issue 2 (5th July 2022) - McDermott, Tom; Clifford, Megan M.; Sherburne, Tim; Horowitz, Barry; Beling, Peter A.
ABSTRACT: Silverfish is a case study of a fictional system of systems of medium complexity. It evaluates the FOREST methodologies referenced in part I of this article series in the contexts of system design, system test and evaluation, and training. The Silverfish case study illustrates implementation of the FOREST meta‐process model and the Mission Aware metamodel described in part I. The case study demonstrates how to accomplish the modeling of functional behaviors and associated derivation of requirements for a realistic system. This article begins with a short description of Silverfish, then describes the outcome of cyber tabletop exercises captured into modeling artifacts, the outcome of a resilience analysis, and a full derivation of cyber resilience functional and performance requirements from the modeling and analysis.